Preventing environmental damage from products : an analysis of the policy and regulatory framework in Europe / edited by Eléonore Maitre-Ekern, University of Oslo, Carl Dalhammar, Lunds University, Hans Christian Bugge, University of Oslo. - Maitre, Eléonore; Dalhammar, Carl; Bugge, Hans Christian (Cambridge University Press, 2018)
How to tackle environmental damage from the throwaway society is one of the defining questions of the twenty-first century. By establishing a circular economy, we can encourage and support sustainable production and consumption. These essays by an international group of leading scholars from a range of disciplines analyse policies and legal instruments and challenge mainstream assumptions, from the choice of a policy mix to the actual effect of imposing standards on the market, and from corporate objectives and priorities to the use of precaution in assessing particularly harmful substances. Each chapter contributes to a better understanding of the current policy and regulatory framework in Europe and identifies the challenges and opportunities ahead. The book breaks new ground by examining how product policies can contribute to important objectives and visions, such as the aims of the circular economy. It is a must-read for researchers as well as for policymakers and practitioners.